Academic outcomes of flipped classroom learning: a meta‐analysis - Chen, Kuo‐Su; Monrouxe, Lynn; Lu, Yi‐Hsuan; Jenq, Chang‐Chyi; Chang, Yeu‐Jhy; Chang, Yu‐Che; Chai, Pony Yee‐Chee (Medical education, 2018)
Context The flipped classroom (FC), reversing lecture and homework elements of a course, is popular in medical education. The FC uses technology‐enhanced pre‐class learning to transmit knowledge, incorporating in‐class interaction to enhance higher cognitive learning. However, the FC model is expensive and research on its effectiveness remains inconclusive. The aim of this study was to compare the efficacy of the FC model over traditional lecture‐based (LB) learning by meta‐analysis. Methods We systematically searched MEDLINE, PubMed, ERIC, CINAHL, EMBASE, reference lists and Association for Medical Education in Europe (AMEE) conference books. Controlled trials comparing academic outcomes between the FC and LB approaches in higher education were considered eligible. The main findings were pooled using a random‐effects model when appropriate. Results Forty‐six studies (9026 participants) were included, comprising four randomised controlled trials (RCTs), 19 quasi‐experimental studies and 23 cohort studies. Study populations were health science (n = 32) and non health science (n = 14) students. The risk of bias was high (36/37 articles). Meta‐analyses revealed that the FC had significantly better outcomes than the LB method in examination scores (post‐intervention and pre–post change) and course grades, but not in objective structured clinical examination scores. Subgroup analyses showed the advantage of the FC was not observed in RCTs, non‐USA countries, nursing and other health science disciplines and earlier publication years (2013 and 2014). Cumulative analysis and meta‐regression suggested a tendency for progressively better outcomes by year. Outcome assessments rarely focused on behaviour change. Conclusions The FC method is associated with greater academic achievement than the LB approach for higher‐level learning outcomes, which has become more obvious in recent years. However, results should be interpreted with caution because of the high methodological diversity, statistical heterogeneity and risk of bias in the studies used. Future studies should have high methodological rigour, a standardised FC format and utilise assessment tools evaluating higher cognitive learning and behaviour change to further examine differences between FC and LB learning. The authors’ meta‐analysis (46 studies, >9000 participants, health and non‐health science education) found flipped classrooms generally have significantly better learning outcomes than lecture learning, with a tendency for better outcomes for more recent studies.